Low-warpage aluminum nitride ceramic and preparation method thereof

By fabricating low-warpage aluminum nitride ceramics with dual gradients in porosity and yttrium aluminum oxide composition, and combining ion implantation and a compressive stress layer, the warpage problem of aluminum nitride substrates during thermal cycling was solved, achieving high flexural strength and low warpage, suitable for high-power electronic packaging and optical communication.

CN121698658APending Publication Date: 2026-03-20JIANGSU BREE OPTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511775511.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Existing aluminum nitride substrates are prone to warping due to thermal stress concentration during reflow soldering and thermal cycling, which affects chip packaging yield and device reliability.

Method used

By preparing low-warpage aluminum nitride ceramics with dual gradients in porosity and yttrium aluminum oxide composition, and combining ion implantation and a compressive stress layer, the porosity and composition gradients of the surface and core regions can be controlled to alleviate thermal expansion stress concentration.

Benefits of technology

We have achieved a warpage of ≤50μm and a flexural strength of ≥320MPa for large-size aluminum nitride ceramics after reflow and thermal cycling, meeting the requirements of high-power electronic packaging and optical communication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides low-warpage aluminum nitride ceramic which comprises a surface layer area and a core area, and the porosity of the surface layer area is 0-0.05%; the porosity of the core area is 0.1%-0.3%; the low-warpage aluminum nitride ceramic also comprises yttrium aluminum oxide; the volume fraction of the yttrium aluminum oxide in the surface layer area is 1.2-2.5 vol%; the volume fraction of the yttrium aluminum oxide in the core region is 3-8 vol%. The invention also discloses a preparation process of the ceramic, the tape casting process and the ion implantation process are carried out on ceramic slurry, and the tape casting process and the ion implantation process have a synergistic effect, so that the low-warpage aluminum nitride ceramic with pore and component double gradients and ion stress regulation is obtained, the warpage of the large-size (100 * 100 * 0.25-0.50) aluminum nitride ceramic is less than or equal to 50 microns after backflow and thermal circulation, and the warpage of the aluminum nitride ceramic is less than or equal to 50 microns. Meanwhile, the breaking strength can still reach 320 MPa or above after multiple times of cold and heat cycles.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electronic packaging materials, in particular to a low-warp aluminum nitride (AlN) ceramic suitable for high-power semiconductor devices, optical communication and the like, and a preparation method thereof. BACKGROUND

[0002] Aluminum nitride (AlN) has become a core substrate material in the fields of high-power electronic packaging, radio frequency modules and the like due to its high thermal conductivity (170-230 W / m·K), low thermal expansion coefficient (≤4.5 ppm / ℃), excellent insulation and compatibility with semiconductor materials. With the development of semiconductor devices towards high power and miniaturization, there is an increasing demand for large-size AlN substrates with a size of 100×100 mm or more. However, such substrates are prone to warp due to thermal stress concentration during reflow soldering (260℃) and thermal cycling (-55 / 150℃), which seriously affects the yield of chip packaging and the reliability of devices.

[0003] Therefore, it is necessary to develop a process to prepare an aluminum nitride ceramic with low warp performance. SUMMARY

[0004] The present application provides a low-warp aluminum nitride ceramic and a preparation method thereof. The ceramic slurry is subjected to a casting process to obtain a three-layer composite blank in the order of A-B-A, and an ion implantation process is performed in the subsequent process. The two processes work together to obtain a low-warp aluminum nitride ceramic with double gradients of porosity and composition and ion stress adjustment. The warp degree of the large-size (100×100×0.25~0.50) aluminum nitride ceramic after reflow and thermal cycling is ≤50 μm, and the bending strength after multiple cold and hot cycles is still above 320 MPa. The prepared aluminum nitride ceramic has large size, low warp degree and high bending strength by the preparation method of the present application.

[0005] In a first aspect, the present application provides a low-warp aluminum nitride ceramic, comprising a surface layer region and a core region. The porosity of the surface layer region is 0~0.05%; the porosity of the core region is 0.1%~0.3%; the surface layer region refers to a region less than or equal to a mm from the surface of the low-warp aluminum nitride ceramic; 0.08≤a≤0.15 mm; the core region refers to a region greater than a from both sides of the surface of the low-warp aluminum nitride ceramic; the low-warp aluminum nitride ceramic comprises yttrium aluminum oxide; the yttrium aluminum oxide comprises Y3Al5O 12The aluminum nitride (ANO) is selected from at least one of YAlO3 and Y4Al2O9; the volume fraction of ANO in the surface region is 1.2-2.5 vol%; and the volume fraction of ANO in the core region is 3-8 vol%. This application, by controlling the porosity and ANO composition within the above-mentioned ranges in both the surface and core regions, enables low-warpage ANO ceramics to possess a dual gradient in both porosity and ANO composition. The low porosity in the surface region helps maintain the flatness of the ANO ceramic, while the appropriate porosity in the core region buffers thermal stress, thereby mitigating thermal expansion. The gradient change in ANO composition between the surface and core regions alleviates stress concentration caused by thermal expansion during thermal cycling, ensuring that the thermal expansion of each region matches, further suppressing warpage of the ANO ceramic. Through the synergistic effect of the dual gradients in porosity and ANO composition, the resulting ANO ceramic can further exhibit large size, low warpage, and high flexural strength.

[0006] In some embodiments, one side surface of the low-warpage aluminum nitride ceramic includes a compressive stress layer, which comprises either magnesium or silicon; the thickness of the compressive stress layer is 10 μm to 50 μm. When one side surface of the low-warpage aluminum nitride ceramic in this application meets this condition, a residual compressive stress layer can be constructed on one side surface of the low-warpage aluminum nitride ceramic to actively counteract the tensile stress generated by thermal cycling, thereby suppressing the warpage of the aluminum nitride ceramic and further enabling the obtained aluminum nitride ceramic to have large size, low warpage, and high flexural strength.

[0007] In some embodiments, low-warpage aluminum nitride ceramics meet the following conditions: (1) The thickness of the low-warpage aluminum nitride ceramic is 0.25 mm to 0.50 mm; preferably, the thickness of the low-warpage aluminum nitride ceramic is 0.32 mm to 0.38 mm. (2) The warpage of the low-warpage aluminum nitride ceramic is 10~45μm; (3) The flexural strength of the low-warpage aluminum nitride ceramic is 320~400MPa; When the low-warpage aluminum nitride ceramic in this application meets the above conditions, the resulting aluminum nitride ceramic can have large size, low warpage, and high flexural strength.

[0008] Secondly, this application provides a method for preparing low-warpage aluminum nitride ceramics, comprising the following steps: Step S1: Mix plasticizer, binder, and organic solvent in a mass ratio of 0.6~0.8:1:2~3 to obtain a transparent colloid; Step S2, the dispersant, the powder, the organic solvent are mixed according to the mass ratio of 0.01~0.03:1:0.3~0.7, wherein the powder includes aluminum nitride powder and sintering aid; the sintering aid, the dispersant, the organic solvent are pre-mixed and ball milled for 1~2h; then the aluminum nitride powder is added and ball milled for 6~12h, to obtain a first slurry; Step S3, the transparent colloid and the powder (aluminum nitride powder and sintering aid) are added into the first slurry according to the mass ratio of 0.5~0.7:1, wherein the powder includes aluminum nitride powder and sintering aid, and ball milling is performed for 8~12h to obtain a second slurry; Step S4, the second slurry and the pore-forming agent are ball milled according to the mass ratio of the pore-forming agent to the aluminum nitride in the second slurry for 1~3h, to obtain a ceramic slurry A and a ceramic slurry B respectively; wherein in the ceramic slurry A, the pore-forming agent and the aluminum nitride in the first slurry are ball milled according to the mass ratio of 0~0.05:1; wherein in the ceramic slurry B, the pore-forming agent and the aluminum nitride in the second slurry are ball milled according to the mass ratio of 0.1~0.3:1; Step S5, the ceramic slurry A and the ceramic slurry B are subjected to a flow casting process to obtain a three-layer composite green body in the order of A-B-A; Step S6, after the three-layer composite green body is subjected to staged degassing, heat preservation is performed in a nitrogen atmosphere, ion implantation and annealing are performed after the heat preservation process, to obtain a low-warp aluminum nitride ceramic. Based on the above scheme, the low-warp aluminum nitride ceramic with double gradients of porosity and yttrium aluminum oxide composition and ion stress adjustment can be obtained, and the prepared aluminum nitride ceramic can have large size, low warp, and high bending strength.

[0009] In some embodiments, the mass percentage of the sintering aid in the first slurry is 0.8~1.5%, and the mass percentage of the sintering aid in the second slurry is 3.3~3.9%.

[0010] In some embodiments, the flow casting process satisfies: the ceramic slurry A and the ceramic slurry B are sequentially subjected to flow casting in the order of A-B-A; or the ceramic slurry A and the ceramic slurry B are respectively subjected to flow casting to obtain A green body and B green body, and then the A and B green bodies are stacked in the order of A-B-A and subjected to hot pressing or warm isostatic pressing. Based on the scheme of the flow casting process, the porosity and yttrium aluminum oxide composition of the low-warp aluminum nitride ceramic in the surface region and the core region can satisfy the above relationship, and the prepared aluminum nitride ceramic can have large size, low warp, and high bending strength.

[0011] In some embodiments, the ion implantation process satisfies at least one of the following conditions: (1) the implanted ions include at least one of magnesium or silicon; (2) The voltage is 50~150keV; (3) The ion implantation process adopts surface ion implantation, and the implanted ion density is 1×10⁻⁶. 13 ~1×10 15 cm -2 .

[0012] When the ion implantation process meets this condition, this application enables one side surface of the low-warpage aluminum nitride ceramic to include a compressive stress layer, and enables the compressive stress layer to meet the above condition, so that the prepared aluminum nitride ceramic can have large size, low warpage, and high flexural strength.

[0013] In some embodiments, the plasticizer includes one of dibutyl phthalate, dioctyl phthalate, and polyethylene glycol; the sintering aid includes one or more of Y₂O₃ and YF₂; the pore-forming agent includes one or more of polyvinyl alcohol, polyethylene glycol, ammonium bicarbonate, polymethyl methacrylate, or graphite spheres; the dispersant includes at least one of oleic acid, herring oil, BYK111, and BYK163; and the organic solvent includes one or more of xylene, toluene, ethanol, isopropanol, and n-butanol. When these conditions are met, the resulting aluminum nitride ceramic can have large dimensions, low warpage, and high flexural strength.

[0014] In some embodiments, the adhesive satisfies at least one of the following conditions: (1) The adhesive includes at least one of polyvinyl butyral and polyacrylic acid resin; (2) Based on the mass of the powder, wherein the powder includes aluminum nitride powder and sintering aid, and the mass percentage of the binder is 6-8%.

[0015] When the binder meets these conditions, the resulting aluminum nitride ceramics can have large size, low warpage, and high flexural strength.

[0016] In some embodiments, the staged glue removal process includes the following steps: Step S1, with an airflow of 40~50m³ / h 3 The first stage of glue removal is carried out at a temperature of 300~400℃ and a time of 1~2h. Step S2, with an airflow rate of 40~50m³ / h 3 The second stage of glue removal is carried out at a temperature of 450~500℃ and a time of 1~2h. Step S3, with an airflow rate of 40~50m³ / h 3 The third stage of glue removal is carried out at a temperature of 600~700℃ for 3~4 hours per hour.

[0017] When the debinding process meets this condition, the resulting aluminum nitride ceramics can have large size, low warpage, and high flexural strength.

[0018] In some embodiments, the conditions for the heat preservation process include: a nitrogen atmosphere, a temperature of 1700~1800℃, and a time of 2~4 hours. When the heat preservation process meets these conditions, the resulting aluminum nitride ceramic can have large size, low warpage, and high flexural strength.

[0019] In some embodiments, the annealing process conditions include: a nitrogen atmosphere, a temperature of 800~1200°C, and a time of 1~3 hours. When the annealing process meets these conditions, the resulting aluminum nitride ceramic can have large size, low warpage, and high flexural strength. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0021] Example 1 1. Preparation of ceramic slurries A and B Step S1: Mix the plasticizer dibutyl phthalate, the binder polyvinyl butyral, and the organic solvent toluene in a mass ratio of 0.7:1:2.3 to obtain PVB transparent colloidal polyvinyl butyral resin. Step S2: Mix the dispersant oleic acid, powder, and organic solvent toluene at a mass ratio of 0.015:1:0.4, wherein the powder includes aluminum nitride powder and sintering aid Y2O3 powder; premix the sintering aid Y2O3 powder, dispersant oleic acid, and organic solvent toluene and ball mill for 2 hours; then add the aluminum nitride powder and ball mill for 6 hours to obtain the first slurry, wherein the mass percentage of the sintering aid in the first slurry is 1.1%; Step S3: PVB transparent colloid and powder are added to the first slurry at a mass ratio of 0.7:1, wherein the powder includes aluminum nitride powder and sintering aid Y2O3 powder. The mixture is ball-milled for 12 hours to obtain the second slurry, wherein the sintering aid accounts for 3.6% of the mass of the second slurry. Step S4: The second slurry and the pore-forming agent are ball-milled for 3 hours according to the mass ratio of the pore-forming agent to the aluminum nitride in the second slurry to obtain ceramic slurry A and ceramic slurry B, respectively. In ceramic slurry A, the pore-forming agent polyvinyl alcohol and the aluminum nitride powder in the first slurry are ball-milled at a mass ratio of 0.01:1. In ceramic slurry B, the pore-forming agent ammonium bicarbonate and the aluminum nitride powder in the second slurry are ball-milled at a mass ratio of 0.12:1. 2. Casting process The ceramic slurry was cast sequentially in the order ABA. First, a 0.11 mm thick preform, denoted as film A, was cast onto a polyethylene terephthalate (PET) film strip. Ceramic slurry B was then cast onto the 0.11 mm film A to obtain a 0.24 mm thick film B. Next, another 0.11 mm thick film was cast onto the 0.35 mm thick double-layer film strip using ceramic slurry A, resulting in a three-layer composite film with a total thickness of 0.46 mm. After the three-layer film was cast, it was cut into 160 × 160 mm square preforms.

[0022] 3. The phased glue removal process includes the following steps: Step S1, with an airflow of 40m³ / h 3 The first stage of glue removal was carried out at a heating rate of 0.45℃ / min, a temperature of 300℃, and a time of 1 hour. Step S2, with an airflow of 40m³ / h 3 The second stage of glue removal was carried out at a heating rate of 0.2℃ / min, a temperature of 450℃, and a time of 1h. Step S3, with an airflow of 40m³ / h 3 The third stage of glue removal is carried out at a temperature of 600℃, a heating rate of 0.18℃ / min, and a time of 3 hours; after glue removal, an edge weight of 4kg is added.

[0023] 4. Insulation process The process involves maintaining the temperature at 1800℃ in a nitrogen atmosphere for 4 hours.

[0024] 5. Ion implantation process At a voltage of 100 keV, aluminum nitride ceramics were implanted with 1×10⁻⁶ surface ions. 14 cm -2 Mg ions.

[0025] 6. Annealing process The low-warpage aluminum nitride ceramic of this embodiment is obtained by annealing in a nitrogen atmosphere at a temperature of 1000°C for 1 hour.

[0026] The low-warpage aluminum nitride ceramic of this embodiment includes a surface region and a core region. The porosities of the surface region and the core region are shown in Table 1. The surface region refers to the region less than or equal to 0.11 mm from the surface of the low-warpage aluminum nitride ceramic. The core region refers to the region greater than 0.11 mm from both sides of the low-warpage aluminum nitride ceramic. The low-warpage aluminum nitride ceramic includes yttrium aluminum oxide. The yttrium aluminum oxide includes Y3Al5O 12The volume fractions of yttrium aluminum oxide in the surface and core regions are shown in Table 1. One surface of the low-warpage aluminum nitride ceramic includes a compressive stress layer comprising magnesium; the thickness of the compressive stress layer is 30 μm. The thickness of the low-warpage aluminum nitride ceramic is 0.46 mm.

[0027] Example 2 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 1 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 96.95%, the mass percentage of sintering aid is 3%, and the mass percentage of pore-forming agent is 0.05%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 90.7%, the mass percentage of sintering aid is 9%, and the mass percentage of pore-forming agent is 0.3%; the heat preservation process is: temperature 1740℃, time 4h; the ion implantation process is: voltage 80keV, implantation 1×10 14 cm -2 Mg ions; Annealing process: nitrogen atmosphere, temperature 900℃, time 2h.

[0028] Example 3 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 2 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 97.97%, the mass percentage of sintering aid is 2%, and the mass percentage of pore-forming agent is 0.03%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 94.8%, the mass percentage of sintering aid is 5%, and the mass percentage of pore-forming agent is 0.2%; the heat preservation process is carried out at a temperature of 1770℃ for 4 hours; the annealing process is carried out in a nitrogen atmosphere at a temperature of 1000℃ for 2 hours.

[0029] Example 4 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Embodiment 3 in the casting process: ceramic slurry A and ceramic slurry B are cast into blanks with thicknesses of 0.11 mm and 0.24 mm, respectively. Blanks A and B are stacked in three layers according to the ABA sequence and subjected to hot isostatic pressing at 80°C and 90 MPa for 30 min to obtain a three-layer composite film with a thickness of 0.46 mm. After forming, it is cut into square blanks of 160×160 mm.

[0030] Example 5 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 4 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 98.97%, the mass percentage of sintering aid is 1%, and the mass percentage of pore-forming agent is 0.03%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 90.8%, the mass percentage of sintering aid is 9%, and the mass percentage of pore-forming agent is 0.2%; the heat preservation process is: temperature 1790℃, time 4h.

[0031] Example 6 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 4 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 96.97%, the mass percentage of sintering aid is 3%, and the mass percentage of pore-forming agent is 0.03%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 96.3%, the mass percentage of sintering aid is 3.5%, and the mass percentage of pore-forming agent is 0.2%; the heat preservation process is: temperature 1780℃, time 4h.

[0032] Example 7 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 4 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 95.97%, the mass percentage of sintering aid is 4%, and the mass percentage of pore-forming agent is 0.03%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 95.3%, the mass percentage of sintering aid is 4.5%, and the mass percentage of pore-forming agent is 0.2%; the heat preservation process is: temperature 1775℃, time 4h.

[0033] Example 8 The low-warpage aluminum nitride ceramic of this embodiment differs from that of Example 4 in that, in the preparation of ceramic slurries A and B, based on the mass of ceramic slurry A, the mass percentage of aluminum nitride in ceramic slurry A is 97.97%, the mass percentage of sintering aid is 2%, and the mass percentage of pore-forming agent is 0.03%; based on the mass of ceramic slurry B, the mass percentage of aluminum nitride in ceramic slurry B is 94.8%, the mass percentage of sintering aid is 5%, and the mass percentage of pore-forming agent is 0.2%; the heat preservation process is: temperature 1770℃, time 4h.

[0034] Example 9 The difference between the low-warpage aluminum nitride ceramic of this embodiment and that of Embodiment 4 is that the aluminum nitride ceramic is annealed directly after heat preservation without ion implantation.

[0035] Comparative Example 1 Compared with the preparation method of Example 1, the difference is as follows: In the preparation of ceramic slurry B, based on the mass of ceramic slurry B, the mass ratio of aluminum nitride in ceramic slurry B is 97.11%, the mass ratio of sintering aid is 2.8%, and the mass ratio of pore-forming agent is 0.09%; the heat preservation process is: the temperature is 1800℃ and the time is 6h.

[0036] Comparative Example 2 Compared with the preparation method of Example 3, the difference is that in the preparation of ceramic B, based on the mass of ceramic slurry B, the mass ratio of aluminum nitride in ceramic slurry B is 88.7%, the mass ratio of sintering aid is 11%, and the mass ratio of pore-forming agent is 0.3%.

[0037] Comparative Example 3 Compared with the preparation method of Example 3, the difference is that in the preparation of ceramic slurry A, based on the mass of ceramic slurry A, the mass ratio of aluminum nitride is 97.94%, the mass ratio of sintering aid is 2%, and the mass ratio of pore-forming agent is 0.06%.

[0038] Comparative Example 4 Compared with the preparation method of Example 4, the difference is that: during the casting process, ceramic slurry A and ceramic slurry B are cast into blanks with thicknesses of 0.24 mm and 0.11 mm, respectively. Blanks A and B are stacked in three layers in the BAB sequence and isostatically pressed at 80°C and 90 MPa for 30 min to obtain a three-layer composite film with a thickness of 0.46 mm. After forming, it is cut into square blanks of 160×160 mm.

[0039] Comparative Example 5 Compared with the preparation method of Example 4, the difference is that: during the casting process, ceramic slurry A and ceramic slurry B are cast into blanks with thicknesses of 0.14 mm and 0.32 mm, respectively. Blanks A and B are stacked in the order of AB and then isostatically pressed at 80°C and 90 MPa for 30 min to obtain a two-layer composite film with a thickness of 0.46 mm. After forming, it is cut into square blanks of 160×160 mm.

[0040] Comparative Example 6 Compared with the preparation method in Example 4, the difference is in the following: the heat preservation process: the temperature is 1680℃ and the time is 6h.

[0041] Comparative Example 7 Compared with the preparation method in Example 3, the difference is in the following: the heat preservation process: the temperature is 1820℃ and the time is 4h.

[0042] Test case The aluminum nitride ceramics from each embodiment and comparative example were laser-cut into 100×100×0.32mm samples for porosity testing, yttrium aluminum oxide testing, warpage testing, and flexural strength testing. Porosity testing was performed using micro-CT to measure the porosity of the surface and core regions of the substrate. Yttrium aluminum oxide testing was conducted using backscattered SEM and ImageProplus software to measure the volume fraction of yttrium aluminum oxide. Warpage testing was performed on the aluminum nitride ceramics using a laser warpage meter under the conditions of three reflow soldering cycles at 260℃ and 1000 cycles of thermal cycling from -55℃ to 150℃. Flexural strength testing was performed using a universal testing machine under the same conditions: three reflow soldering cycles at 260℃ and 1000 cycles of thermal cycling from -55℃ to 150℃.

[0043] Table 1

[0044] Table 2

[0045] As shown in Tables 1 and 2, by controlling the porosity of the surface region and the volume fraction of yttrium aluminum oxide in the core region within the aforementioned ranges, the resulting aluminum nitride ceramic can exhibit low warpage and high flexural strength. In particular, when the volume fraction of yttrium aluminum oxide in the surface region is controlled to be 1.2–2.5 vol%, and the volume fraction of yttrium aluminum oxide in the core region is controlled to be 3–8 vol%, the resulting aluminum nitride ceramic can exhibit low warpage and high flexural strength. Specifically, when the porosity of the surface region is controlled to be 0–0.05%, and the porosity of the core region is controlled to be 0.1%–0.3%, the resulting aluminum nitride ceramic can further exhibit low warpage and high flexural strength.

[0046] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the principles of this application should be included within the protection scope of this application.

Claims

1. A low-warpage aluminum nitride ceramic, characterized in that, The material includes a surface region and a core region. The porosity of the surface region is 0~0.05%; the porosity of the core region is 0.1%~0.3%. The surface region refers to the region less than or equal to a mm from the surface of the low-warpage aluminum nitride ceramic; 0.08≤a≤0.15mm. The core region refers to the region greater than a mm from both sides of the low-warpage aluminum nitride ceramic. The low-warpage aluminum nitride ceramic comprises yttrium aluminum oxide; the yttrium aluminum oxide comprises Y3Al5O 12 At least one of YAlO3 and Y4Al2O9; the volume fraction of the yttrium aluminum oxide in the surface region is 1.2 to 2.5 vol%; the volume fraction of the yttrium aluminum oxide in the core region is 3 to 8 vol%.

2. The low-warpage aluminum nitride ceramic according to claim 1, characterized in that, One side surface of the low-warpage aluminum nitride ceramic includes a compressive stress layer, which includes either magnesium or silicon. The thickness of the compressive stress layer is 10μm~50μm.

3. The low-warpage aluminum nitride ceramic according to claim 1, characterized in that, The low-warpage aluminum nitride ceramic meets the following conditions: (1) The thickness of the low-warpage aluminum nitride ceramic is 0.25 mm to 0.50 mm; preferably, the thickness of the low-warpage aluminum nitride ceramic is 0.32 mm to 0.38 mm. (2) The warpage of the low-warpage aluminum nitride ceramic is 10~45μm; (3) The flexural strength of the low warp aluminum nitride ceramic is 320~400MPa.

4. The method for preparing low-warpage aluminum nitride ceramic according to any one of claims 1 to 3, characterized in that, Includes the following steps: Step S1: Mix plasticizer, binder, and solvent in a mass ratio of 0.6~0.8:1:2~3 to obtain a transparent colloid; Step S2: Mix the dispersant, powder, and solvent at a mass ratio of 0.01~0.03:1:0.3~0.7, wherein the powder includes aluminum nitride powder and sintering aid; premix the sintering aid, the dispersant, and the organic solvent and ball mill for 1~2 hours; then add the aluminum nitride powder and ball mill for 6~12 hours to obtain the first slurry; Step S3: Add the transparent colloid and powder to the first slurry at a mass ratio of 0.5~0.7:1, wherein the powder includes aluminum nitride powder and sintering aid, and ball mill for 8~12 hours to obtain the second slurry; Step S4: The second slurry and the pore-forming agent are ball-milled for 1-3 hours according to the mass ratio of the pore-forming agent to the aluminum nitride in the second slurry to obtain ceramic slurry A and ceramic slurry B respectively; wherein, in ceramic slurry A, the pore-forming agent and the aluminum nitride in the first slurry are ball-milled at a mass ratio of 0-0.05:1; wherein, in ceramic slurry B, the pore-forming agent and the aluminum nitride in the second slurry are ball-milled at a mass ratio of 0.1-0.3:

1. Step S5: Perform a casting process on the ceramic slurry A and the ceramic slurry B to obtain a three-layer composite green body with an ABA sequence; Step S6: After the three-layer composite preform is debonded in stages, it is kept at a high temperature in a nitrogen atmosphere. After the heat preservation process, ion implantation and annealing are performed to obtain low warpage aluminum nitride ceramic.

5. The method for preparing low-warpage aluminum nitride ceramic according to claim 4, characterized in that, The casting process satisfies the following conditions: ceramic slurry A and ceramic slurry B are cast sequentially in the order of ABA; or, ceramic slurry A and ceramic slurry B are cast into A green body and B green body respectively, and then A and B green bodies are stacked in the order of ABA, followed by hot pressing or warm isostatic pressing.

6. The method for preparing low-warpage aluminum nitride ceramic according to claim 4, characterized in that, The ion implantation process satisfies at least one of the following conditions: (1) The implanted ions include at least one of magnesium or silicon; (2) The voltage is 50~150keV; (3) The ion implantation process adopts surface ion implantation, and the implanted ion density is 1×10⁻⁶. 13 ~1×10 15 cm -2 .

7. The method for preparing low-warpage aluminum nitride ceramic according to claim 6, characterized in that, The plasticizer includes one of dibutyl phthalate, dioctyl phthalate, and polyethylene glycol; the sintering aid includes one or more of Y2O3 and YF2; the pore-forming agent includes one or more of polyvinyl alcohol, polyethylene glycol, ammonium bicarbonate, polymethyl methacrylate, or graphite balls; the dispersant includes at least one of oleic acid, herring oil, BYK111, and BYK163; and the organic solvent includes one or more of xylene, toluene, ethanol, isopropanol, and n-butanol.

8. The method for preparing low-warpage aluminum nitride ceramic according to claim 7, characterized in that, The adhesive satisfies at least one of the following conditions: (1) The adhesive includes at least one of polyvinyl butyral and polyacrylic acid resin; (2) Based on the mass of the powder, wherein the powder is aluminum nitride powder and sintering aid, the mass ratio of the binder is 6~8%.

9. The method for preparing low-warpage aluminum nitride ceramic according to claim 8, characterized in that, The phased glue removal process includes the following steps: Step S1, with an airflow of 40~50m³ / h 3 The first stage of glue removal is carried out at a temperature of 300~400℃ and a time of 1~2h. Step S2, with an airflow rate of 40~50m³ / h 3 The second stage of glue removal is carried out at a temperature of 450~500℃ and a time of 1~2h. Step S3, with an airflow rate of 40~50m³ / h 3 The third stage of glue removal is carried out at a temperature of 600~700℃ for 3~4 hours per hour.

10. The method for preparing low-warpage aluminum nitride ceramic according to claim 9, characterized in that, The conditions for the heat preservation process include: a nitrogen atmosphere, a temperature of 1700~1800℃, and a time of 2~4 hours.

11. The method for preparing low-warpage aluminum nitride ceramic according to claim 10, characterized in that, The conditions for the annealing process include: a nitrogen atmosphere, a temperature of 800~1200℃, and a time of 1~3h.